Identifying scenarios for the own risk and solvency assessment of insurance companies - Philipp Aigner (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2023)
Most insurers in the European Union determine their regulatory capital requirements based on the standard formula of Solvency II. However, there is evidence that the standard formula inaccurately reflects insurers' risk situation and may provide misleading steering incentives. In the second pillar, Solvency II requires insurers to perform a so-called 'Own Risk and Solvency Assessment' (ORSA). In their ORSA, insurers must establish their own risk measurement approaches, including those based on scenarios, in order to derive suitable risk assessments and address shortcomings of the standard formula. The idea of this paper is to identify scenarios in such a way that the standard formula in connection with the ORSA provides a reliable basis for risk management decisions. Using an innovative method for scenario identification, our approach allows for a simple but relatively precise assessment of marginal and even non-marginal portfolio changes. We numerically evaluate the proposed approach in the context of market risk employing an internal model from the academic literature and the Solvency Capital Requirement (SCR) calculation under Solvency II.
Keywords: G22; G28; G32; 330; Risk measurement; Enterprise Risk Management; Own Risk and Solvency Assessment; Solvency II